2014
DOI: 10.1136/thoraxjnl-2014-206260.451
|View full text |Cite
|
Sign up to set email alerts
|

M270 Obtaining Information When You Have A Rare Disease - The Potential For Ipf Support Groups

Abstract: taking oxygen therapy. Patients may be left with feelings of anger at missed opportunities and concern for lost years of intervention and appropriate palliative care support. Conclusions The diagnosis of IPF is a devastating one, which can be challenging to manage. Carers, patient groups and expert support at diagnosis were found to be invaluable to patients during this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(M55, 74 years, P)DiscussionDifferent sources for different needs Patients affected by a rare disease as well as their relatives use a variety of different sources to keep themselves informed. In accordance with previous quantitative studies, among others, especially the internet, patient associations as well as specialist doctors play an important role when gathering information[11][12][13][14]. However, to date, it has been unclear what experiences patients with a rare disease and their families have had when they have used these types of sources, how they assess them, and how their value changes over time.From our interviews, it was shown that initially after diagnosis, when the need for information is very high, only few patients obtained detailed and profound information from their doctors.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…(M55, 74 years, P)DiscussionDifferent sources for different needs Patients affected by a rare disease as well as their relatives use a variety of different sources to keep themselves informed. In accordance with previous quantitative studies, among others, especially the internet, patient associations as well as specialist doctors play an important role when gathering information[11][12][13][14]. However, to date, it has been unclear what experiences patients with a rare disease and their families have had when they have used these types of sources, how they assess them, and how their value changes over time.From our interviews, it was shown that initially after diagnosis, when the need for information is very high, only few patients obtained detailed and profound information from their doctors.…”
mentioning
confidence: 63%
“…However, still little is known about how people affected by a rare disease and their families search for information. Previous studies may be outdated, have relied on few single sources, focused on specific information needs only, and did not focus on rare diseases in general [10][11][12][13][14][15]. A recent study from Teixeira et al [13] on patients with a rare blood disorder shows that specialists are of particularly great importance when it comes to sources that were widely used for information gathering.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for patients and their relatives, the latter are important contact partners that help them access specialized care or offer advice on all questions relating to their disease. For people affected by a rare disease, physicians can be another important source of information [ 8 - 12 ]. However, apart from those who deal with these conditions on a regular basis, for instance, physicians working in centers for rare diseases, general practitioners, as well as specialists in private practice often lack such information.…”
Section: Introductionmentioning
confidence: 99%
“…However, still little is known about how people affected by a rare disease and their families search for information. Previous studies may be outdated, have relied on few single sources, focused on specific information needs only, and did not focus on rare diseases in general [19][20][21][22][23][24]. Teixeira et al [22] conducted a questionnaire survey of 1019 patients with a rare blood disorder, which showed that medical specialists are of particularly great importance when it comes to sources that were widely used for information gathering.…”
Section: Introductionmentioning
confidence: 99%